"Gasta's Law "The Legal Dimension and the Political Dimension - Najdawi, Mohammed Hadi Younes (Journal of Economic, Administrative and Legal Sciences, 2018)
The subject of the jasta law has taken up a great space of discussion both by researchers and by international law scholars or in the media and social media, because it contains surprises that have not yet been discovered to can be understood and put it on the correct way. this law has appeared in a turbulent context (veto power exercised by former president barrack Obama), did not prevent it from being issued, and it is not yet known the main target of it, although many researchers believe that it targets Saudi Arabia’s funds. there is no doubt that this law has repercussions that will affect international relations as a whole and reconsider the concept and foundations of international law.the study concluded that this law was not issued arbitrarily but was issued to establish the cases beyond and draw for a different American vision in the region. therefore, we recommend the need to intensify efforts to prevent the dangers of this law, so that countries that have their place in the international community declare their rejection of this irresponsible decision and stand in solidarity with the states that may affect them.
Keywords: JASTA law; USA; Saudi Arabia; terrorism; international law